2017
DOI: 10.1146/annurev-med-051215-030919
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Effective Ebola Virus Vaccine

Abstract: Long-term control of viral outbreaks requires the use of vaccines to impart acquired resistance and ensuing protection. In the wake of an epidemic, established immunity against a particular disease can limit spread and significantly decrease mortality. Creation of a safe and efficacious vaccine against Ebola virus (EBOV) has proven elusive so far, but various inventive strategies are now being employed to counteract the threat of outbreaks caused by EBOV and related filoviruses. Here, we present a current over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 58 publications
(96 reference statements)
0
32
0
Order By: Relevance
“…Ebola virus causes a hemorrhagic fever that is often lethal, with case fatality rates approaching 90% in past outbreaks. 20,21 While recent progress in vaccine development and use of biologics, such as antibodies, for therapeutic and prophylactic purposes show promise,22 small molecule drugs still offer many advantages, including ease of delivery, lower cost, and longer shelf life. The ~120 residue IID of VP35 is a particularly appealing drug target for combating Ebola and other viruses in the Filoviridae family given that it has a well-conserved sequence and plays multiple essential roles in the viral lifecycle.23 One of its primary functions is to antagonize a host's innate immunity, particularly RIG-I-like receptor (RLR)-mediated detection of viral nucleic acids, to prevent an interferon (IFN) response and signaling of neighboring cells to heighten their antiviral defenses.24-26 Crystal structures have provided a foundation for understanding much about the mechanism of VP35-mediated IFN antagonism.27,28 For example, they have revealed that VP35's IID binds both the blunt ends and backbone of doublestranded RNA (dsRNA), and that there is a PPI between these dsRNA-binding modes ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Ebola virus causes a hemorrhagic fever that is often lethal, with case fatality rates approaching 90% in past outbreaks. 20,21 While recent progress in vaccine development and use of biologics, such as antibodies, for therapeutic and prophylactic purposes show promise,22 small molecule drugs still offer many advantages, including ease of delivery, lower cost, and longer shelf life. The ~120 residue IID of VP35 is a particularly appealing drug target for combating Ebola and other viruses in the Filoviridae family given that it has a well-conserved sequence and plays multiple essential roles in the viral lifecycle.23 One of its primary functions is to antagonize a host's innate immunity, particularly RIG-I-like receptor (RLR)-mediated detection of viral nucleic acids, to prevent an interferon (IFN) response and signaling of neighboring cells to heighten their antiviral defenses.24-26 Crystal structures have provided a foundation for understanding much about the mechanism of VP35-mediated IFN antagonism.27,28 For example, they have revealed that VP35's IID binds both the blunt ends and backbone of doublestranded RNA (dsRNA), and that there is a PPI between these dsRNA-binding modes ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, very few genetic changes may result in human-pathogenic Reston viruses (13). Since the discovery of the first two members of the Ebolavirus family in 1976 in Sudan (today South Sudan) and Zaïre (today Democratic Republic of Congo), Ebolaviruses had until 2013 only caused small outbreaks in humans affecting up to a few hundred individuals (4,5). The recent Ebola virus outbreak in West Africa (2013–2016) resulted in 28,616 confirmed, probable, and suspected cases of Ebola virus disease and 11,310 deaths (5), which may still underestimate the actual numbers (6).…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of the first two members of the Ebolavirus family in 1976 in Sudan (today South Sudan) and Zaïre (today Democratic Republic of Congo), Ebolaviruses had until 2013 only caused small outbreaks in humans affecting up to a few hundred individuals (4,5). The recent Ebola virus outbreak in West Africa (2013–2016) resulted in 28,616 confirmed, probable, and suspected cases of Ebola virus disease and 11,310 deaths (5), which may still underestimate the actual numbers (6). It was the first Ebolavirus outbreak that affected multiple countries, was introduced to another country via air travel, and resulted in disease cases outside of Africa (4,5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations